Dinâmica populacional de quatro espécies de Dysdercus (Hemiptera, Pyrrhocoridae) e a fenologia das plantas hospedeiras - Almeida,J. R. de (1993)
The food cycle and geographical variation of Dysdercus diet were studied as strategy elements of trophic resources exploitation. The species used were D. fulvoniger, D. maurus, D. mendesi and D. ruficollis. A random sampling method was adopted at two regular sampling areas (Vassouras and Itaguaí, Rio de Janeiro, Brazil). The places sampled only once were selected based on the potential migration of Dydercus. Various transects were determined, with 99 places; these transects involved six morpho-climatic-phytogeographical domains: Atlantic Tropical, Cerrado, Caatinga, Amazonic Equatorial, Pantanal and "Planalto das Araucárias". The food cycle of Dysdercus at Vassouras is based on the exploitation of reproductive structures (flowerand fruit) of some Malvaceae, Boraginaceae, Compositae and Cucurbitaceae. The total diet includes other host plant structures. Fifty-three plant species (16 families) are explored as food by the insect along the 99 places of sampling. The habitats of Dysdercus are characterized by climatic variations, geographical distribution and phenology of host plants, and also by the dispersion of seeds.